Thermal, mechanical and microstructural analysis of concrete containing microencapsulated phase change materials - Dehdezi, Pejman Keikhaei; Hall, Matthew R.; Dawson, Andrew R.; Casey, Sean P. (Taylor & Francis, 2012)
This paper studies the thermal, mechanical and microstructural aspects of concrete containing different amounts of microencapsulated phase change materials (PCMs). In addition, numerical simulation is carried out to study the potential application of PCM-modified concrete for reduction in summer surface temperature. It is shown that increasing PCM content in concrete led to lower thermal conductivity and an increase in the heat storage ability of concrete. However, the compressive and flexural strength of concrete significantly decreased. Microstructural analysis showed that PCMs appear to remain intact during mixing; however, PCM particles appear to fail by bursting under loading, creating hemispherical voids and crack initiation points as well as possible entrapped air behaviour. The result of numerical simulation revealed that reduction in summer concrete pavement surface temperature by several degrees was possible, with implications for reduction in concrete thermal stresses, shrinkage and urban heat island effect.